Polypeptide derivative, nanofiber and application of polypeptide derivative and nanofiber in preparation of product for repairing subfissure of teeth

By using the nano fiber hydrogel formed by the use of polypeptide derivatives to solve the problem of the complexity and biological risk of the existing dental fissure therapy technology, the orderly mineral crystal formation of the glaze and dental cracks is achieved , Significantly improved the effect of fracture fracture.

CN119331052APending Publication Date: 2025-01-21TIANJIN DENTAL HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411373414.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing dental cryptoclase treatment technology has problems such as high trauma, complex material synthesis, complex usage methods, high cost and biotoxicity risks.

Method used

Using a polypeptide derivative, the sequence is served as NAP-PHE-PHE-GLY-HIS-THR-LYS-GLU, which forms nano-fiber hydrogel by self-assembly, which is used to induce glaze and dental cracking. Mineral crystal formation.

Benefits of technology

The formation of orderly mineral crystals at the glazed and dental cracks is achieved, which significantly improves the effects of dental fissure repair, and the chemical structure of the material is clear, low cost, and good biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331052A_ABST
    Figure CN119331052A_ABST
Patent Text Reader

Abstract

The invention discloses a polypeptide derivative, a nanofiber and application of the polypeptide derivative and the nanofiber in preparation of a product for repairing subfissure of teeth, the sequence of the polypeptide derivative comprises Nap-Phe-Phe-Gly-Asp-His-Thr-Lys-Glu, and Nap is 2-naphthylacetic acid. The polypeptide derivative is clear in chemical structure, small in molecular weight, single in component, simple in preparation process, low in cost, high in yield and easy to store. The polypeptide derivative disclosed by the invention is self-assembled in an aqueous solution to form the supramolecular hydrogel with a nanofiber microstructure, and the supramolecular hydrogel is high in stability and good in biocompatibility. The nanofiber hydrogel of the polypeptide derivative can interact with mineral ions and can form a crystal structure very close to natural hydroxyapatite, so that ordered formation of mineral crystals is induced at enamel and dentin hidden cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical engineering, and in particular to a polypeptide derivative, a nanofiber and applications thereof in preparing a product for repairing tooth cracks. Background Art

[0002] Cracked teeth are a common oral disease and have become the third leading cause of tooth loss. Early management of cracked teeth is of great significance for maintaining the integrity of tooth structure, ensuring tooth function, and avoiding severe pulp and periapical lesions. At present, the management strategies for cracked teeth mainly include three categories: immediate treatment such as adjusting the jaw to eliminate occlusal interference, reducing the cusp inclination to reduce the splitting force, and acid etching and enamel adhesive light curing treatment; ring protection and full crown restoration treatment; balancing the occlusal force burden of the whole mouth, treating and extracting other affected teeth in the whole mouth, and repairing missing teeth. The cracks of cracked teeth often pass through the enamel to the dentin. In recent years, studies have used polyelectrolytes and nanocomposites to form mineralized deposits in enamel and dentin cracks. However, the above methods have relatively large trauma, complex material synthesis and preparation processes, complex methods of use, high costs, and excessive use will cause biological toxicity.

[0003] In the study of biomimetic remineralization, proteins or peptides play a very important role. Functional peptide fragments in the primary sequence of functional proteins play a key regulatory role in the mineralization process. At the same time, the secondary structure of proteins, especially the folding and coiling mode of protein polypeptide chains, can significantly change the function of proteins and affect the biomineralization process. In this context, the role of self-assembling functional peptides in the mineralization process has attracted widespread attention. The β-folded structure makes the polypeptide chain almost completely unfolded, greatly increasing the probability of carboxyl and phosphate groups in amino acid residues contacting and binding with calcium ions, thereby inducing and promoting the mineralization process. At the same time, the β-folded structure can affect the structural relationship, stereochemistry and electrostatic potential of crystals, and affect the deposition of calcium salts macroscopically. Studies have found that an egg white peptide Asp-His-Thr-Lys-Glu has a high affinity for calcium ions and can bind to calcium ions through the carboxyl groups of Asp and Glu, the δ-N in the imidazole ring of His, and the ε-amino nitrogen of Lys. Current studies have shown that supramolecular hydrogels formed by self-assembly of bioactive peptide derivatives through non-covalent interactions can significantly prolong their half-life, improve bioavailability, and even simulate the biological functions of proteins. They have the advantages of clear chemical structure, easy synthesis, low cost, good biocompatibility, and strong stability, and have shown broad application prospects in fields such as regenerative medicine. Summary of the invention

[0004] The purpose of the present invention is to provide a polypeptide derivative to address the technical defects in the existing cracked tooth treatment technology.

[0005] Another object of the present invention is to provide a nanofiber hydrogel based on the above polypeptide derivatives.

[0006] Another object of the present invention is to provide an application of the above-mentioned nanofiber hydrogel in the preparation of a product for repairing tooth cracks.

[0007] The technical solution adopted to achieve the purpose of the present invention is:

[0008] A polypeptide derivative, the sequence of which includes Nap-Phe-Phe-Gly-Asp-His-Thr-Lys-Glu, wherein Nap is 2-naphthylacetic acid.

[0009] In the above technical solution, the polypeptide derivative includes a D-configuration polypeptide derivative, and the structural formula of the D-configuration polypeptide derivative is as follows:

[0010]

[0011] In the above technical solution, the polypeptide derivative includes an L-configuration polypeptide derivative, and the structural formula of the L-configuration polypeptide derivative is as follows:

[0012]

[0013] In the above technical solution, the preparation method of the polypeptide derivative comprises the following steps:

[0014] Step 1, the C-terminus of Fmoc-Glu is bound to a solid phase support resin, that is, the carboxyl end of Glu is connected to a solid phase support resin;

[0015] Step 2, removing the Fmoc protecting group of the amino acid, washing with DMF, and drying;

[0016] Step 3, the C-terminus of the next Fmoc-amino acid (Fmoc-Lys) is coupled to the N-terminus of the amino acid coupled to the resin, and washed;

[0017] Step 4, repeating steps 2 and 3, sequentially performing amino acid coupling until Fmoc-FFG-DHTKE is connected to the solid phase support resin, removing the Fmoc protecting group, and washing;

[0018] Step 5, coupling 2-naphthylacetic acid with the N-terminus of the polypeptide on the solid phase support resin, washing, and cutting off from the resin to obtain a crude product of the polypeptide derivative;

[0019] Step 6, purifying the crude product of the polypeptide derivative using a high performance liquid chromatography, and freeze-drying to obtain the polypeptide derivative.

[0020] Another aspect of the present invention also includes a nanofiber hydrogel based on the polypeptide derivative, which is prepared by the following steps: adding the polypeptide derivative to a PBS solution, heating until the polypeptide derivative is completely dissolved, adjusting the pH to 7.0-8.0, and cooling to room temperature to obtain a nanofiber hydrogel of the polypeptide derivative.

[0021] In the above technical solution, the pH is adjusted with sodium carbonate solution or hydrochloric acid solution.

[0022] Another aspect of the present invention also includes the use of the nanofiber hydrogel of the polypeptide derivative in the preparation of a product for repairing cracked teeth.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The polypeptide derivative of the present invention has a clear chemical structure, a small molecular weight, a single component, a simple preparation process, a low cost, a high yield, and is easy to store. The polypeptide derivative of the present invention self-assembles in an aqueous solution to form a supramolecular hydrogel with a microstructure of nanofibers, which has strong stability and good biocompatibility. The nanofiber hydrogel of the polypeptide derivative can interact with mineral ions to form a crystal structure very close to natural hydroxyapatite, thereby inducing orderly mineral crystal formation at hidden cracks in enamel and dentin. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a mass spectrometry analysis diagram, wherein a is Nap-FFG-DHTKE of Example 1, and b is Nap- D F D FG-DHTKE.

[0026] Figure 2 are optical photographs, wherein a is the nanofiber hydrogel of the L-configuration polypeptide derivative of Example 3, and b is the nanofiber hydrogel of the D-configuration polypeptide derivative of Example 4.

[0027] Figure 3 It is a transmission electron microscope picture, wherein a is the nanofiber hydrogel of the L-configuration polypeptide derivative of Example 3, and b is the nanofiber hydrogel of the D-configuration polypeptide derivative of Example 4.

[0028] Figure 4 It is a circular dichroism spectrum, wherein a is the nanofiber hydrogel of the L-configuration polypeptide derivative of Example 3, and b is the nanofiber hydrogel of the D-configuration polypeptide derivative of Example 4.

[0029] Figure 5The scanning electron micrographs show the effects of inducing human enamel remineralization to repair tooth cracks, wherein a is the nanofiber hydrogel of the L-configuration polypeptide derivative of Example 3, b is the nanofiber hydrogel of the D-configuration polypeptide derivative of Example 4, c is the control group, and d is the blank group.

[0030] Figure 6 This is an energy spectrum analysis diagram of inducing human enamel remineralization to repair tooth crack deposits, wherein a is the nanofiber hydrogel of the L-configuration polypeptide derivative of Example 3, and b is the control group.

[0031] Figure 7 This is a diagram of a biosafety evaluation experiment in which the nanofiber hydrogel of the polypeptide derivative is composited with human gingival fibroblasts and cultured for one day.

[0032] Figure 8 This is a diagram of the biosafety evaluation experiment of culturing human gingival fibroblasts with the polypeptide derivative nanofiber hydrogel for 4 days.

[0033] Fig. 9 This is a diagram of the biosafety evaluation experiment of the polypeptide derivative nanofiber hydrogel composite human gingival fibroblasts cultured for 7 days. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] Example 1

[0036] A method for synthesizing an L-configuration polypeptide derivative (Nap-FFG-DHTKE) comprises the following steps:

[0037] Step 1, put 2 g of 2-Cl(Trt)-Cl resin (solid phase support resin) into a 150 mL reactor, add DCM solvent to soak for 30 min to swell, take out the resin and wash it with DMF, then drain the resin, and repeat this 4 times.

[0038] Step 2, add 0.6 mmol of Fmoc-Glu(OtBu)-OH (the first amino acid at the C-terminus) + DCM and DIEA into the reactor, and place the reactor in a shaker at 30° C. for reaction for 2 hours.

[0039] Step 3, add 0.5 mL of DIEA, 0.5 mL of MEOH and 2 mL of DCM (DIEA:MEOH:DCM=1:1:2) into the reactor using a pipette, react for 20 min, block the unreacted groups on the resin, wash the resin with DMF, and then drain the resin, repeat this 4 times.

[0040] Step 4, add an appropriate amount of 20% piperidine solution (piperidine / DMF=1:4) to the reactor, which is 3 times the volume of the resin, react for 20 minutes, remove the Fmoc protecting group, wash with DMF 4 times after deprotection, and then drain.

[0041] Step 5, take 10 to 20 resins from the reactor with a long-necked pipette and detect them using the ninhydrin method. If the resin has color, it means that the deprotection is successful; if it does not show color, repeat the deprotection-washing-detection operation.

[0042] Step 6, add 1.8 mmol Fmoc-Lys(Boc)-OH + 1.8 mmol HOBT into the reactor, add an appropriate amount of DMF as the reaction solvent, and finally add an appropriate amount of DIC into the reactor. Place the reactor in a shaker at 30°C for 1 hour, wash the resin with DMF, and then drain the resin. Repeat this process 4 times.

[0043] Step 7, take 10 to 20 resins in the reactor with a long-necked pipette and detect them using the ninhydrin method. If the resin has color, it means that the condensation is incomplete, and continue the reaction in step 6; if the resin is colorless, it means that the reaction is complete.

[0044] Step 8, repeat steps 4 to 7 until the last amino acid is coupled, wash with DMF 4 times, and wash with DCM for the last time, and finally drain the resin to obtain FFG-DHTKE resin peptide.

[0045] Step 9, 2-naphthylacetic acid is coupled to the N-terminus of the resin peptide and washed to obtain Nap-FFG-DHTKE resin peptide.

[0046] Cleavage of Nap-FFG-DHTKE resin peptide:

[0047] Place 10 ml ± 2 ml of a cleavage reagent containing H2O, TFA, EDT and TIS in a volume ratio of 95:1:2:2 in a cleavage reaction bottle, add 1 g of Nap-FFG-DHTKE resin peptide to the cleavage reaction bottle while stirring at 0-10°C, and after the system temperature stabilizes, continue stirring and reacting at 20-25°C for 2 hours to release the polypeptide derivative from the 2-Cl(Trt)-Cl resin, filter out the cleavage solution, and precipitate it with 5 times the volume of the concentrated solution in icy ether, filter out the precipitate and dry it under reduced pressure at room temperature to obtain a crude polypeptide derivative product.

[0048] Purification and Lyophilization:

[0049] Step 1: Dissolve the crude product of the polypeptide derivative in acetonitrile and water, filter it, and purify it by Shimadzu semi-preparative high performance liquid chromatography. Separate and purify it by using a suitable gradient at room temperature to obtain an L-configuration polypeptide derivative. Detect the mass spectrometry and in-process purity analysis, such as Figure 1 As shown in a, it can be seen from the figure that the observed molecular weight of the L-configuration polypeptide derivative is 1148.30, its theoretical molecular weight is 1148.25, and the purity is 96.636%, >95%, which meets the requirements. Therefore, the results show that the L-configuration polypeptide derivative was successfully synthesized and can be used in subsequent experiments.

[0050] Step 2, after converting the L-configuration polypeptide derivative to hydrochloride, collecting the target peak, detecting and analyzing, the L-configuration polypeptide derivative containing the qualified target peak is freeze-dried under reduced pressure to obtain a powdered L-configuration polypeptide derivative (Nap-FFG-DHTKE), and the powdered L-configuration polypeptide derivative is qualified in QA detection and set aside.

[0051] Example 2

[0052] A D-type peptide derivative (Nap- D F D The synthesis method of FG-DHTKE comprises the following steps:

[0053] The L-configuration Fmoc-Phe in Example 1 was changed to the D-configuration, and the other steps remained unchanged, and finally the D-configuration polypeptide derivative (Nap- D F D FG-DHTKE), such as Figure 1 b is the mass spectrometry analysis of the D-configuration polypeptide derivative. The results show that the observed molecular weight of the D-configuration polypeptide derivative is 1147.65, the theoretical molecular weight is 1148.25, and the purity is 97.813%, >95%, which meets the requirements. Therefore, the D-configuration polypeptide derivative was successfully synthesized and can be used for subsequent experiments.

[0054] Example 3

[0055] This example provides a nanofiber hydrogel based on the L-configuration polypeptide derivative (Nap-FFG-DHTKE) described in Example 1, which is prepared by the following steps:

[0056] Weigh 2.3 mg of the purified L-configuration polypeptide derivative and place it in a 2 mL glass bottle. Add 1 mL of PBS solution (pH = 7.4) and heat until the polypeptide derivative is completely dissolved. Adjust the pH value to about 7.4 with sodium carbonate solution. After cooling to room temperature, an invertible L-configuration polypeptide derivative nanofiber hydrogel is obtained, which is recorded as L-gel. Figure 2 As shown in a, it is an optical photograph of the hydrogel formed by heating and cooling the L-configuration polypeptide derivative (Nap-FFG-DHTKE). Whether the gel is formed or not is determined by methods known in the art, such as the method of inverting the bottle. After the bottle is inverted, the hydrogel is retained at the bottom of the bottle, and if it flows, it is liquid and has not been gelled.

[0057] Example 4

[0058] This embodiment provides a D-configuration polypeptide derivative (Nap- D F D The nanofiber hydrogel of FG-DHTKE) was prepared by the following steps:

[0059] The D-configuration polypeptide derivative obtained in Example 2 was prepared by the steps of Example 3 to obtain a nanofiber hydrogel of an invertible D-configuration polypeptide derivative, which was recorded as D-gel. Figure 2 b is an optical photograph of the nanofiber hydrogel of the D-configuration polypeptide derivative.

[0060] Test Example 1

[0061] Transmission electron microscopy observation of the microscopic morphology of nanofiber hydrogels of hydrogel polypeptide derivatives:

[0062] Use a pipette to take 10 μL of the nanofiber hydrogel of the L-configuration polypeptide derivative of Example 3 and the nanofiber hydrogel of the D-configuration polypeptide derivative of Example 4, respectively, and drop them on the copper mesh. After 10 seconds, use filter paper to absorb the excess sample; then take 10 μL of deionized water and drop it on the copper mesh for washing. After 10 seconds, use filter paper to absorb the excess water. Repeat the above steps twice to ensure that the hydrogel stained on the copper mesh is a single layer; take 10-15 μL of uranyl acetate and also drop it on the copper mesh stained with the sample, stain it for 1 minute, and then use filter paper to absorb it; wash it again with water twice to prevent excessive staining. Mark the copper mesh, place it in a dryer, and perform relevant tests using a transmission electron microscope after it is completely dried. The results are as follows Figure 3 shown. Figure 3 The a in the figure shows the microstructure of the nanofiber hydrogel of the L-configuration polypeptide derivative, which presents a nanofiber structure with uniform diameter and interwoven into a network. Figure 3 The microstructure of the nanofiber hydrogel of the D-configuration polypeptide derivative is shown in b, where the nanofibers are in the form of strips of similar length and uneven thickness.

[0063] Test Example 2

[0064] Circular dichroism detection of the secondary structure of nanofiber hydrogels of hydrogel polypeptide derivatives:

[0065] The nanofiber hydrogel of the L-configuration polypeptide derivative of Example 3 and the nanofiber hydrogel of the D-configuration polypeptide derivative of Example 4 (both concentrations were 0.5 mM) were filtered using a 0.22 μm filter, and the filtrate was collected with an EP tube as the test solution. Before the test, nitrogen was introduced into the circular dichroism spectrometer for 30 minutes at a temperature of 25°C, and the test solution was placed in a 0.1 cm quartz cuvette. The scanning wavelength range was 190 to 260 nm, and the scanning speed was 1 nm / s. This was repeated three times, and the obtained data was imported into the drawing software. The results are shown in FIG. Figure 4 As shown, Figure 4 a in the figure is the secondary structure of the nanofiber hydrogel of the L-configuration polypeptide derivative, which has a positive peak at 200 nm and a negative peak at 238 nm, indicating that it has a secondary structure similar to β-folding; Figure 4 Figure b is the secondary structure of the nanofiber hydrogel of the D-configuration polypeptide derivative, and its positive and negative peaks are relatively inconspicuous.

[0066] Example 5

[0067] Experimental evaluation of the efficacy of peptide derivative nanofiber hydrogel in inducing human enamel remineralization to repair tooth cracks:

[0068] Preparation of cracked tooth block samples: Freshly extracted premolars and molars that needed to be extracted for orthodontic treatment or could not be retained due to periodontal disease were collected. Inclusion criteria: The crown cracks were not easy to identify with the naked eye but were visible under the root canal microscope, and were confirmed by two senior clinicians, and there was no caries, no tooth defects, no tooth filling or root canal filling. Exclusion criteria: The tooth surface cracks were obvious and visible to the naked eye; the tooth surface had caries, tooth defects or fillings, inlays, crown restorations, etc. Gently remove pollutants, dental calculus, and periodontal membranes on the tooth surface, and place the cracked tooth block samples in 0.1wt% thymol solution before use. The cracks of the samples were examined by optical microscopy and the positions were marked. The cracked areas were cut into tooth blocks using a low-speed cutter, ultrasonically cleaned for 3 minutes, and placed in a 0.1wt% thymol solution for later use.

[0069] Prepare artificial saliva: Mix 1.5mmol / L CaCl2, 0.9mmol / L KH2PO4, 130mmol / L KCl, 1.0mmol / LNaN3 and 20mmol / L HEPES solution evenly, and adjust the pH to 7.0 with 1mol / L KOH.

[0070] After etching the cracked tooth block samples with 35% wt phosphoric acid solution for 30 seconds, the cracked tooth blocks were randomly divided into 4 groups: Group a: 0.5 mM nanofiber hydrogel of L-configuration polypeptide derivative was evenly applied on the cracked tooth blocks using an applicator stick, and the application was repeated for 3 minutes, and the surface of the cracked tooth blocks was dried at room temperature; Group b: 0.5 mM nanofiber hydrogel of D-configuration polypeptide derivative was evenly applied on the surface of the cracked tooth blocks using an applicator stick, and the application was repeated for 3 minutes, and the surface was dried at room temperature; Group c (control group): deionized water was evenly applied on the cracked tooth blocks using an applicator stick, and the application was repeated for 3 minutes, and the surface was dried at room temperature; Group d (blank group): the treatment method was the same as that of group c; the cracked tooth blocks of groups a, b and c were placed in a well plate filled with 3 ml of the above-mentioned artificial saliva, and the artificial saliva was replaced every 24 hours, and the cracked tooth blocks of group d were placed in a well plate filled with 3 ml of deionized water, and the artificial saliva was replaced every 24 hours. Scanning electron microscopy observation and energy spectrum analysis after 7 days of mineralization, the results of scanning electron microscopy are as follows Figure 5 As shown, Figure 5 In the figure a, the nanofiber hydrogel group of L-configuration polypeptide derivatives is shown. It can be seen that needle-like deposits are formed at the cracks, and the cracks are healed. Figure 5 b is the nanofiber hydrogel group of D-configuration peptide derivatives, where needle-like deposits can be seen on the enamel surface, while the cracks are still empty; Figure 5 The c in the figure is the control group, where large deposits are formed on the enamel surface, but the cracks are still clearly visible; Figure 5 The d in the figure is the blank group, and no deposits were observed on the enamel surface and cracks. Figure 6 As shown: Figure 6 a in the figure is a nanofiber hydrogel group of L-configuration polypeptide derivatives, which has a high calcium and phosphorus content, and a Ca / P ratio of about 1.58. Figure 6 B is the control group, which has very low calcium and phosphorus content, high potassium and chloride content, and a K / Cl ratio of about 0.98.

[0071] Biosafety (cytotoxicity) evaluation experiment of nanofiber hydrogels of peptide derivatives:

[0072] The nanofiber hydrogel of the L-configuration polypeptide derivative of Example 3 and the nanofiber hydrogel of the D-configuration polypeptide derivative of Example 4 were added to the culture medium to prepare concentrations of 125 μM, 250 μM, 500 μM, and 1000 μM, respectively, for use.

[0073] Human gingival fibroblasts were cultured with DMEM containing 10% fetal bovine serum culture fluid. When the cells reached 80% aggregation, the cells were seeded on a 96-well plate at a density of 5000 cells / well and cultured for 24 hours. The culture medium was replaced with a similar culture medium containing the nanofiber hydrogel of the L-configuration polypeptide derivative and the nanofiber hydrogel of the D-configuration polypeptide derivative prepared above at different concentrations. Each concentration of each hydrogel was an experimental group, and a control group and a blank group were set up. Each group was set up with 4 parallel groups and cultured again for 24 hours. Among them, the control group was the same culture medium without hydrogel, and the blank group was the same culture medium without hydrogel and cells. Cytotoxicity was detected after constant temperature culture in an incubator for 1, 4, and 7 days. Cytotoxicity was detected using a CCK-8 kit, and the absorbance of each group was measured by an enzyme marker at a wavelength of 450nm.

[0074] Calculate cell viability. The calculation formula is: Cell viability (%) = [OD (experimental) - OD (blank)] / [OD (control) - OD (blank)] × 100%. Results: From Figure 7-Figure 9 It can be seen that the relative cell survival rate of each experimental group is relatively high, indicating that the nanofiber hydrogel of the L-configuration polypeptide derivative of Example 3 and the nanofiber hydrogel of the D-configuration polypeptide derivative of Example 4 of the present invention are non-cytotoxic at 0.5 mM and are safe to use.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polypeptide derivative, characterized in that: The sequence of the polypeptide derivative includes Nap-Phe-Phe-Gly-Asp-His-Thr-Lys-Glu, wherein Nap is 2-naphthylacetic acid.

2. The polypeptide derivative according to claim 1, characterized in that: The polypeptide derivatives include D-configuration polypeptide derivatives, and the structural formula of the D-configuration polypeptide derivatives is as follows:

3. The polypeptide derivative according to claim 1, characterized in that: The polypeptide derivatives include L-configuration polypeptide derivatives, and the structural formula of the L-configuration polypeptide derivatives is as follows:

4. The polypeptide derivative according to claim 1, characterized in that: The preparation method of the polypeptide derivative comprises the following steps: Step 1, the C-terminus of Fmoc-Glu is bound to a solid phase support resin, that is, the carboxyl end of Glu is connected to a solid phase support resin; Step 2, removing the Fmoc protecting group of the amino acid, washing with DMF, and drying; Step 3, the C-terminus of the next Fmoc-amino acid (Fmoc-Lys) is coupled to the N-terminus of the amino acid coupled to the resin, and washed; Step 4, repeating steps 2 and 3, sequentially performing amino acid coupling until Fmoc-FFG-DHTKE is connected to the solid phase support resin, removing the Fmoc protecting group, and washing; Step 5, coupling 2-naphthylacetic acid with the N-terminus of the polypeptide on the solid phase support resin, washing, and cutting off from the resin to obtain a crude product of the polypeptide derivative; Step 6, purifying the crude product of the polypeptide derivative using a high performance liquid chromatography, and freeze-drying to obtain the polypeptide derivative.

5. A nanofiber hydrogel based on the polypeptide derivative according to any one of claims 1 to 4, characterized in that: The nanofiber hydrogel is prepared by the following steps: adding a polypeptide derivative into a PBS solution, heating until the polypeptide derivative is completely dissolved, adjusting the pH to 7.0-8.0, and cooling to room temperature to obtain a nanofiber hydrogel of the polypeptide derivative.

6. The nanofiber hydrogel according to claim 5, characterized in that: Adjust the pH with sodium carbonate solution or hydrochloric acid solution.

7. Use of the nanofiber hydrogel as claimed in claim 6 in preparing a product for repairing tooth cracks.